Multinational Firms, Technology and Location - Pehr-Johan Norbäck (The Research Institute of Industrial Economics (IUI), 1999)
This paper analyzes a three-stage optimization problem in which a firm chooses (i) its technology, by deciding on a level of R&D, (ii) whether this technology is to be used in a domestic or in a foreign plant and (iii) the quantity produced and sold on the market. If technology transfer costs are low, 'high-tech' or R&D-intensive firms tend to produce abroad. At higher technology transfer costs, high-tech firms tend to export. An empirical analysis using a data set of Swedish multinational firms, confirms the latter prediction.
Keywords: F23; L13; O33; 330; Multinational Firms; R&D; Location; Empirical Analyses; Multinationales Unternehmen; Industrieforschung; Betriebliche Standortwahl; Nash-Gleichgewicht; Theorie